Use of phytotherapy in pediatric respiratory diseases - Cristina Munteanu (Amaltea Medical Publishing House, 2022)
Herbal medicine is a mild and well-tolerated alternative treatment method that could be used to treat pediatric respiratory ailments. Medicinal plants such as captalan, geranium, turmeric or echinacea have been shown in numerous studies to have the ability to significantly improve the respiratory function of pediatric patients and may thus be a viable alternative to conventional treatments in acute and chronic respiratory diseases.